The relationship between servant leadership, team commitment, team citizenship behaviour and team effectiveness : an exploratory study - Mahembe, Bright (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2010.